Role of Prostaglandins in Neuroinflammatory and Neurodegenerative Diseases - Lima, Isabel Vieira de Assis (Hindawi Publishing Corporation, 2012)
Increasing data demonstrates that inflammation participates in the pathophysiology of neurodegenerative diseases. Among the different inflammatory mediators involved, prostaglandins play an important role. The effects induced by prostaglandins might be mediated by activation of their known receptors or by nonclassical mechanisms. In the present paper, we discuss the evidences that link prostaglandins, as well as the enzymes that produce them, to some neurological diseases.